The audit of the teaching programs of French as a foreign language: The case of the Department of French at the University of Salahaddin, Erbil. - Ali Saleh Malo (Zanco Journal of Humanity Sciences)
Our current research will aim to analyze the teaching programs of French as a foreign language in the French Department, as well as the division of classes into successive sequences, 1st, 2nd, 3rd and 4th year. On the one hand, we will try to consider how this division corresponds to the levels of the Common European Framework of Reference for Languages (CEFRL) ? Similarly, we will attempt to illustrate the problem of heterogeneity of Kurdish students' levels in French classes. To do this, we will take part in measuring the extent of these problems, implementing concrete solutions to reduce or even eradicate them to improve their level, and developing the teaching/learning system in the Department.